Ultrastructural and cytochemical analysis of physic nut callus tissue in response to different combinations of growth regulators - Santos, Dalilhia Nazaré dos; Nunes, Claudinéia Ferreira; Soares, Joyce Dória Rodrigues; Alves, Eduardo; Labory, Cláudia Regina Contijo; Pasqual, Moacir; Pio, Leila Aparecida Salles (Acta Scientiarum. Agronomy, 2015)
This study aimed to induce callus formation in Jatropha curcas L. and to evaluate the ultrastructure and cytochemical behavior of the calli. Calluses were induced with 2,4-D, picloram-PIC, kinetin (Kin) and BAP: (1) control; (2) 4.52 µM 2,4-D; (3) 9.04 µM 2,4-D; (4) 4.14 µM PIC; (5) 8.28 µM PIC; (6) 4.52 µM 2,4-D + 2.32 µM KIN; (7) 9.04 µM 2,4-D + 4.64 µM KIN; (8) 4.14 µM PIC + 2.32 µM KIN; (9) 8.28 µM PIC + 4.64 µM KIN; (10) 4.52 µM 2,4-D + 2.22 µM BAP; (11) 9.04 µM 2,4-D + 4.44 µM BAP; (12) 4.14 µM PIC + 2.22 µM BAP and (13) 8.28 µM PIC + 4.44 µM BAP. It was evaluated the percent coverage of the explants by callus (% CEC) and performed scanning electron microscopy (SEM) and acetocarmine/Evans blue double staining to analyze the embryogenic potential of the calli. As shown by scanning electron microscopy and acetocarmine/Evans blue staining, we found that J. curcas callus formation was optimal with 4.52 µM of 2,4-D.